HIV seroconversion and associated factors among seronegative pregnant women attending ANC in Ethiopia: an institution-based cross-sectional study - Dessale, Dawit Sisay; Gebremariam, Mulugeta Betre; Wolde, Asrat Arja (Frontiers in Reproductive Health, 2024)
Background: In countries with limited resources, including Ethiopia, HIV is diagnosed using a rapid serological test, which does not detect the infection during the window period. Pregnant women who test negative for HIV on the first test may seroconvert throughout pregnancy. Women who are seroconverted during pregnancy may not have received interventions, as they are considered HIV-negative unless they are retested for HIV at the end of their pregnancy. Due to limited data on HIV seroconversion, this study aimed to measure the extent of HIV seroconversion and to identify associated factors among seronegative pregnant women attending ANC in Ethiopia. Methods: Institution-based cross-sectional study was conducted among HIV-negative pregnant women attending the ANC in Ethiopia between June and July 2020. Socio-demographic, clinical, and behavioral data were collected through face-to-face questionnaires and participants’ records review. HIV retesting was performed to determine the current HIV status of pregnant women. The data collected were entered into Epi data version 4.4.1 and were exported and analyzed by SPSS version 25. A p-value < 0.25 in the bivariate analysis was entered into multivariable logistic regression analysis and a p-value of < 0.05 was considered statistically significant. Result: Of the 494 pregnant women who tested negative for HIV on their first ANC test, six (1.2%) tested positive on repeat testing. Upon multivariable logistic regression, pregnant women who have had a reported history of sexually transmitted infections [AOR=7.98; 95% CI (1.21, 52.82)], participants' partners reported travel history for work frequently [AOR=6.00; 95% CI (1.09, 32.99)], and sexually abused pregnant women [AOR=7.82; 95% CI (1.194, 51.24)] were significantly associated with HIV seroconversion. Conclusion: The seroconversion rate in this study indicates that pregnant women who are HIV-negative in early pregnancy are at an ongoing risk of seroconversion throughout their pregnancy. Thus, this study highlights the benefit of a repeat HIV testing strategy in late pregnancy, particularly when the risk of seroconversion or new infection cannot be convincingly excluded. Therefore, repeated testing of HIV-negative pregnant women in late pregnancy provides an opportunity to detect seroconverted pregnant women to enable the timely use of ART to prevent mother-to-child transmission of HIV infection.